The efficacy and safety of 5-fluorouracil/cisplatin/vincristine as a multi-agent chemotherapy regimen in gestational trophoblastic neoplasia - Wang, Lu; Wang, Qian; Xu, Zhen; Yang, Linli; Wang, Wuliang (Frontiers in Oncology, 2023)
Objective: To determine the efficacy and safety of the 5-fluorouracil (5-FU), cisplatin, and vincristine (FPV) chemotherapy regimen in patients with gestational trophoblastic neoplasia (GTN).We performed a retrospective study of 96 GTN patients with International Federation of Gynecology and Obstetrics (FIGO) scores of 5 or greater in the Second Affiliated Hospital of Zhengzhou University from October 2013 to October 2019, including 54 patients who received FPV chemotherapy and 42 who received 5-FU/actinomycin D/vincristine (FAV) chemotherapy. A pulsed intravenous device was used to administer 5-FU. The clinical characteristics, adverse events and response rate were compared between the groups.The patients in the FPV and FAV groups received a total of 228 and 190 courses of chemotherapy, respectively.Complete response (CR) was found in 88.89% (48/54) and 90.48% (38/42) of patients in the FPV group and FAV group, respectively (P=0.801). Both chemotherapy regimens yielded CR in all low-risk patients (100% vs. 100%), whereas 86.67% and 88.24% of high-risk patients achieved CR (FPV vs. FAV, P=0.836), respectively. The most common adverse events (AEs) were myelosuppression and gastrointestinal reactions including neutropenia (83.97%), anemia (60.05%) and nausea (46.41%). In comparison to those in the FAV group, patients in the FPV group reported higher rates of grade 1/2 nausea (53.51% vs. 37.89%, P=0.001), hepatotoxicity (28.95% vs. 17.89%, P=0.008), oral mucositis (23.25% vs. 10.53%, P=0.001) and grade 3/4 neutropenia (47.37% vs. 27.37%, P<0.001), while grade 1/2 diarrhea (7.46% vs. 13.68%, P=0.037) and grade 3/4 oral mucositis (0 vs. 6.32%, P<0.001) were much more common in the FAV group. The rate of overall survival at 5-years was 96.8% in the FPV group and 97.3% in the FAV group (P=0.760), whereas the 5-year disease-free survival rates were 95.9% and 93.9% (P=0.754), respectively.The FPV and FAV regimens with pulsed intravenous 5-FU yielded comparable CR rates and tolerability in patients with GTN with FIGO scores of > 5. Further randomized controlled trials are warranted to validate their efficacy.